1999
DOI: 10.1161/01.cir.99.20.2658
|View full text |Cite
|
Sign up to set email alerts
|

Augmented Short- and Long-Term Hemodynamic and Hormonal Effects of an Angiotensin Receptor Blocker Added to Angiotensin Converting Enzyme Inhibitor Therapy in Patients With Heart Failure

Abstract: for the Vasodilator Heart Failure Trial (V-HeFT) Study Group* Background-ACE inhibitors may not adequately suppress deleterious levels of angiotensin II in patients with heartfailure. An angiotensin receptor blocker added to an ACE inhibitor may exert additional beneficial effects. Methods and Results-Eighty-three symptomatic stable patients with chronic heart failure receiving long-term ACE inhibitor therapy were randomly assigned to double-blind treatment with valsartan 80 mg BID, valsartan 160 mg BID, or pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
103
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(105 citation statements)
references
References 32 publications
2
103
0
Order By: Relevance
“…In patients with stable CHF, small studies have shown that combined RAS blockade provided greater benefit than singlesite blockade on surrogate end points such as improvement in cardiac load and function, 44 increase in exercise capacity, 45 prevention of LV remodeling, and reduction of neurohormonal activation. 35 All these clinical studies share the same limitations: short treatment periods, small group sizes, administration of a nonstandardized ACE inhibitor treatment that was not at a predetermined maximal dose, and the use of a single fixed dose of an AT1R antagonist.…”
Section: Hf and Post-mi: Clinical Resultsmentioning
confidence: 99%
“…In patients with stable CHF, small studies have shown that combined RAS blockade provided greater benefit than singlesite blockade on surrogate end points such as improvement in cardiac load and function, 44 increase in exercise capacity, 45 prevention of LV remodeling, and reduction of neurohormonal activation. 35 All these clinical studies share the same limitations: short treatment periods, small group sizes, administration of a nonstandardized ACE inhibitor treatment that was not at a predetermined maximal dose, and the use of a single fixed dose of an AT1R antagonist.…”
Section: Hf and Post-mi: Clinical Resultsmentioning
confidence: 99%
“…The addition of an ARB to ACEI therapy for heart failure has been shown to have improved neurohormonal, hemodynamic, and left ventricular remodeling effects. 16,17 However, the Valsartan Heart Failure Trial (Val-Heft) reported no difference in mortality outcomes with the combined use of the ARB valsartan with the ACEI captopril compared to ACEI or ARB alone. 26 The rate of adverse events requiring drug discontinuation was significantly higher in the combination drug group than ACEI or ARB group alone; almost half of all patients required a dose reduction and approximately one-quarter required permanent cessation of combination therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Reports suggest favorable effects on hemodynamic parameters, left ventricular remodeling, and neurohormonal activity in patients with chronic heart failure. 16,17 Concerns have been raised however as to whether combination therapy, particularly with the addition of ARB to ACEI, β-blocker, and aldosterone antagonist is associated with excessive neuroendocrine inhibition. 18 -20 The Candesartan in Heart Failure: Assessment of Reduction in Mortality and Morbidity (CHARM)-Added trial demonstrated improved clinical outcomes in heart failure patients on combination therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Baruch and cols. found a decrease in the pulmonary capillary pressure and a tendency toward a decrease in the peripheral vascular resistance 6 to 12 hours after the administration of valsartan in patients without ACEI 11 . The hemodynamic improvement occurs two hours after the ingestion of losartan, with an 18% decrease in the peripheral vascular resistance and a 25% increase in the cardiac index 12 .…”
Section: Binkley Et Almentioning
confidence: 92%